Three‐dimensional ultrashort echo time imaging with tricomponent analysis for human cortical bone. Issue 1 (7th March 2019) - Lu, Xing; Jerban, Saeed; Wan, Lidi; Ma, Yajun; Jang, Hyungseok; Le, Nicole; Yang, Wenhui; Chang, Eric Y.; Du, Jiang
Abstract : Purpose: To investigate tricomponent analysis of human cortical bone using a multipeak fat signal model with 3D ultrashort TE Cones sequences on a clinical 3T scanner. Methods: Tricomponent fitting of bound water, pore water, and fat content using a multipeak fat spectra model was proposed for 3D ultrashort TE imaging of cortical bone. Three‐dimensional ultrashort TE Cones acquisitions combined with tricomponent analysis were used to investigate bound and pore water T 2 ∗ and fractions, as well as fat T 2 ∗ and fraction in cortical bone. Feasibility studies were performed on 9 human cortical bone specimens with regions of interest selected from the endosteum to the periosteum in 4 circumferential regions. Microcomputed tomography studies were performed to measure bone porosity and bone mineral density for comparison and validation of the bound and pore water analyses. Results: The oscillation of the signal decay was well‐fitted with the proposed tricomponent model. The sum of the pore water and fat fractions from tricomponent analysis showed a high correlation with microcomputed tomography porosity (R = 0.74, P < 0.01). Estimated bound‐water fraction also demonstrated a high correlation with bone mineral density (R = 0.70, P < 0.01). Conclusion: Tricomponent analysis significantly improves the estimation of bound‐water and pore‐water fractions in human cortical bone.